The Impact of EG and DEG Cases on Sales of Over-The-Counter Syrup - Ni Nyoman Yudianti Mendra; Ni Putu Udayana Antari; Nyoman Budiartha Siada; I Gusti Ayu Marwati (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2023)
The Indonesian Food and Drug Authority (BPOM) investigated and listed safe and unsafe syrup products in response to the contamination of Ethylene Glycol (EG) and Diethylene Glycol (DEG), causing Acute Kidney Injury in pediatric patients. Unsafe products were recalled and removed from distribution, leading to uncertainty and panic among the public and significantly impacting over-the-counter syrup sales in several pharmacies. This retrospective observational study assessed the impact of EG and DEG contamination on the sales of over-the-counter syrup in Pharmacy X in South Denpasar. Data from three months before (August to October 18th, 2022) and three months following the official instruction was published (October 19th, 2022 to December 2022) were analyzed using Wilcoxon test. The findings reveal a staggering decline in the sales of over-the-counter syrup by 35,03% (p-value of 0.03). Moreover, there was a notable increase of prescriptions in powder forms. The contamination cases caused panic, resulting in changes in behavior and consumption patterns. Despite the availability of safety information on an official website, public hesitance toward syrup products persists, indicating the need to implement a more effective strategy to address misinformation and restore public trust. Each individual must be responsible for educating the public during crises to prevent the spread of misinformation, ultimately restoring trust and normal consumer behavior. Furthermore, efficient stock management should be implemented to anticipate potential health crises in the future proactively.